Human Computer Interaction Design in Web Based Warehouse Management Systems Using the Task Centered System Design (TCSD) Method - Muhammad Izzan Fieldi; Fathoni; Muhammad Aiman (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
In the digital transformation era, web-based warehouse management systems play an essential role in ensuring operational efficiency, yet their effectiveness depends not only on functional accuracy but also on a user-centered interface design. This study aims to redesign the interface of Company XYZ’s warehouse management system using the Task-Centered System Design (TCSD) method within the Human-Computer Interaction (HCI) framework. TCSD emphasizes mapping real user tasks, analyzing user-centered requirements, prototyping through scenarios, and conducting usability evaluations. Data were collected through direct observation, structured interviews, and literature review, followed by interface prototyping in Figma and testing with the Maze platform. Six main warehouse tasks login, item distribution, returns, receiving, cycle counting, and searching were evaluated with five participants. The results demonstrated a Task Success Rate (TSR) of 100% across all tasks, with the shortest average Time on Task (ToT) for login (7.89 seconds) and item search (8.58 seconds), and the longest for cycle counting (58.10 seconds). Click Rate (CR) and Error Rate (ER) varied depending on task complexity, with login and item search showing higher ER values, which were influenced by predefined task flows. Overall, findings confirm that TCSD yields a practical and measurable design aligned with user workflows, producing an interface that is efficient, user-friendly, and adaptable to warehouse operations. This research contributes to HCI studies by demonstrating the effectiveness of scenario-based design in logistics systems, while also highlighting the need for larger-scale usability testing in future work.